SOCIAL SURVEY ON PERIODONTAL CARE OUTPATIENT VISITS RATE - S.V. MIKLYAEV; O.M. LEONOVA; A.V. SUSHCHENKO; A.V. NOVIKOV (Avicenna Tajik State Medical University, 2021)
Objective: Analysis of the results of a questionnaire survey of patients who applied for periodontal treatment. Methods: 157 patients who applied for periodontal care were surveyed, and the patients were divided by gender and age. The survey questions were divided into blocks to reduce the survey time and simplify the analysis of the results. Additional methods measuring oral hygiene were the Simplified Oral Hygiene Index (OHI-S), Community Periodontal Index of Treatment Needs (CPITN), Sulcus bleeding index (SBI, Mühlemann and Son), papillarymarginal alveolar index (PMA). Results: The proportion of mild periodontitis cases significantly decreased from the age group 20-29 to the age group 60 and above, 70.8% to 0%, respectively (p<0.01). In contrast, moderate and severe periodontitis cases increased in the younger to the senior age groups, from 25.0% to 47.1% and from 4.2% to 52.9%, respectively (p<0.01). At the same time, the peak prevalence of moderate periodontitis was in patients aged 40-49 years (51.2%). The return visits rates statistically significantly increase with age - from 0% of return visits in patients aged 20-29 to 82.2% in the patients over 60 years of age (p<0.01). The proportion of smoking patients decreased with age from 58.3% to 47.0%. However, the peak prevalence of smoking patients (62.8%) was in a group of patients aged 40-49 years (p<0.01). Changes in oral hygiene indices and periodontal indices (OHI-S, CPITN, PMA and SBI) were statistically insignificant (p>0.05) and showed only a growth trend with increasing age. In addition, it was found that women more often (51.6%) sought this dental care than men (48.4%). Conclusion: Periodontal care outpatient visits rates increase in younger to senior age groups, associated with an increase in the severity of the inflammatory periodontal disease. At the same time, for young patients (from 20 to 39 years old), the priority was the elimination of cosmetic defects during periodontal treatment. It should also be noted that not only early visits for periodontal care influence the treatment results but also smoking cessation.